Perkembangan Hasil Pembelajaran dan Psikologi Anak di MI Al-Awwal Palembang - Mardiah Astuti; Mutyati Mutyati; Ibrahim Ibrahim; Rahma Syafridatul Aini; Jihan Alfi; Amelia Amelia; Shevia Indriani (Lembaga Intelektual Muda (LIM) Maluku, 2022)
This article discusses the development of learning outcomes and child psychology at MI Al-Awwal Palembang, focusing on first-grade students. This research is a field study with a qualitative descriptive approach. Data collection methods used in this study included interviews, documentation, and observations. Data analysis techniques involved data collection, data presentation, and data verification stages. The research results indicate that the development of learning outcomes and child psychology is influenced by various factors, including parents, the student's personal characteristics, and the child's environment, both formal and informal. These factors are interconnected and can impact the well-being and success of teaching and child psychology. The role of educational institutions, parents, the community, and teachers in supporting the success of teaching and child psychology is crucial. The importance of collaboration between schools and families in creating an environment that supports the holistic development of children's learning outcomes and psychology is emphasized.